Recent advances in immunomodulation of reproduction - YADAV, M P; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2023)
Modulation of reproductive functions through immunological approach in livestock is fairly a recentdevelopment. Gonadal functions can be suppressed through the use of antifertility vaccin~ developed againstreproductive hormones and gamete antigens (Sperm and zona pellucida of ovum). This concept has been utiliziecjfor immunosterilization of animals. Ovulation rate and reproductive efficiency on the other hand. may be increasedthrough the use offecundity vaccine. Immunization against inhibin has shown promising results for increasingovulation rate and litter size. Immunomodulation of uterine defense is another area currently being under intensiveinvestigation. Immunomodulators may be considered as an alternative therapeutic agent in clinical and subclinicaluterine infections. Trophoblastic protein(s)or interferon purified recently in some oftl1e animal species has potential application in regulation offertility.
Keywords: Hormone vaccine; immunomodulator; inhibin; trophoblastic protein